PENGARUH POHON INDUK CENDANA (Santalum album L) DAN PEMANGKASAN CABANG TERHADAP PERTUMBUHAN TANAMAN DI KEBUN BENIH CENDANA – KIAN RAI IKUN, KABUPATEN BELU, NUSA TENGGARA TIMUR - Wawo, Albertus Husein (Jurnal Teknologi Lingkungan, 2009)
Sandalwood (Santalum album L) is one of the tropic plants that have high economicvalue. Sandalwood exploitation in East Nusa Tenggara province has very longhistory perhaps more than 1000 years therefore unforgetable. Now a dayssandalwood was categorized as rare plant. One of the several ways to conquerthe rare of sandalwood is to build the garden of sandalwood seeds in Kian RaiIkun, Belu Regency. Some steps of these activities are, to inventory the motherseeds trees in Belu and Timur Tengah Utara Regency, seeds collecting, seedgermination and furthermore sandalwood seedlings are planted in the garden ofsandalwood seeds in Kian Rai Ikun, Belu regency. This garden is located about450 m above sea level (asl).On inventory activity were found 5 mother seeds trees located in Biau (Bi) about500 m asl, Alas (Al) 500 m asl, Haitimuk (Ha) 100 m asl, Oesena (Oe) 500 masl and Tialai (Ti) 450 m asl. Planting of sandalwood seedling in this garden arecoordinated to available planting plot. Every planting plot was grown about 200– 250 sandalwood seedlings from the same mother seeds tree. Some activitiesto maintain sandalwood seedling in the garden after planting time are, watering,weeding and pruning the branch. The aim of branch pruning on sandalwoodtrees is to protect the plant from wind disturbance in order not fall down. In ourexperience sandalwood seedling fall down easily if seedling has dense of branchesand leaves.This research was purposed to study the effect of mother seeds trees and branchpruning on sandalwood growth in the field. The result shown that branch pruningdid not give significantly different on sandalwood growth but the mother seedstrees gave significantly different on sandalwood growth in the field during 1 –10 months after pruning. The sandalwood plants from Haitimuk mother seedstree possess the highest in height and branch growth than other plants, while thesandalwood plants from Oesena mother seeds tree possess the lowest in heightand branch growth. The growth of sandalwood in field followed the models oflogistic growth with high determination coefficient about more than 0. 85.